KUALITAS SEMEN BEKU SAPI SIMMENTAL TERHADAP LAMA THAWING YANG DIGUNAKAN DALAM PROGRAM INSEMINASI BUATAN DI KABUPATEN WONOSOBO TAHUN 2020 - Kurniawan, Andika Vicky; Iskandar, Faruq; Zulfanita, Zulfanita (Prosiding University Research Colloquium, 2021)
The purpose of this reserch is to determine the effect of thawing time on mootility, living percentage of spermatozoa, abnormalities of spermatozoa, colour and pH of Simmental cattle frozen semen using water with temperature 26 o C in Wonosobo regency where the daily average temperature is around 14.3 - 26.5 o C. Cattle breeding takes an important role in increasing the nasional cattle population. The Effort to improve the Artifical Insemination (AI) technique is the key of this goals. This research used 25 ministraw (0,25) frozen semen of cattle Simmental from bulls in BIB Lembang. The method of this research is an exsperimental method with a Completely Randomized Design (CRD) with a pattern of 1 x 6, A is the cattle nation namely the Simmental cattle, B is the leght of thawing time in temperature of 26 o C are T1 (5 seconds), T2 (15 seconds), T3 (30 seconds), T4 (60 secons), T5(90 second), and T6 (120 second), and the treatments are repeated 4 times each. In the order to determine the effect between treatments, the Duncan Multiple Range Test (DMRT) is used as the continue test. Based on the results, it is concluded that the thawing technique with different durations has an effect on motility, abnormality and survival rate of frozen semen of Simmental cattle, while the color and pH are not effected. Therefore, the results revealed that the best treatment is found in the T3 treatment in 30 seconds as the time of thawing.